Anemia predicts poor outcomes of COVID-19 in hospitalized patients: A Prospective study in a tertiary care hospital from South India - Rajanna, Avinash Hanbe; Sivasankaran, Ramakrishnan; Krishnegowda, Ravi (Asian Journal of Medical Sciences, 2021)
Background: Hemoglobin plays a vital role in tissue oxygenation. Hence anemia might significantly affect the prognosis of COVID 19 pneumonia, where in there is development of tissue hypoxia due to the disease pathogenesis. Aims and Objectives: To correlate the severity of anemia in COVID 19 patients with disease outcomes in patients admitted in a tertiary care setting. Materials and Methods: The prospective single-center study considered adults patients of both the gender, diagnosed with COVID-19 infection by RT-PCR technique. Necessary demographic, clinical data and Hemoglobin level were collected and selected subjects were followed-up until discharge or death. Subjects were classified as those who survived and succumbed to death. t-test was used for comparing continuous variables and chi-square test for categorical data between the groups. Results: The study included 1212 patients, where in there was a statistically significant correlation between low hemoglobin level and the disease outcome. The hemoglobin levels were significantly lower in patients who died than the patients who were discharged. Conclusion: Severe anemia as noted by low hemoglobin level was associated with higher mortality than subjects with normal hemoglobin.